LINC00883 Promotes Drug Resistance of Glioma Through a microRNA-136/NEK1-Dependent Mechanism - Li, Yongzhe; Gao, Xin (Frontiers in Oncology, 2022)
Objective: Accumulating evidence has highlighted the roles of long noncoding RNAs (lncRNAs) as competitive endogenous RNAs (ceRNAs) of microRNAs (miRNAs) through their binding sites in progression of glioma. Hereby, we aim to explore the role of LINC00883 as a regulator of miR-136 and its targets NIMA-related kinase 1 (NEK1), thus involving in the drug resistance of glioma cells. Methods: Mechanistic investigations by dual-luciferase reporter, RNA pull-down and RIP assays indicated that LINC00883 bound to miR-136, thereby blocking miR-136-induced downregulation of NEK1. Through gain-of-function experiments in U251 cells which presented a high drug resistance, we found that ectopic expression of LINC00883 resulted in increased MRP (encoding multidrug resistance-associated protein), limited cell apoptosis and increased proliferation. Expectedly, depleting LINC00883 yielded tumor-suppressive and anti-chemoresistance effects on U251 cells by increasing miR-136 and inhibiting NEK1. Next, drug-resistant glioma cell line SOWZ1, drug-sensitive glioma cell line SOWZ2, and drug-resistant glioma cell line SOWZ2-BCNU (SOWZ2 cultured in BCNU) were applied to validate the roles of LINC00883 in the regulation of multi-drug resistance. Results: LINC00883 knockdown suppressed the viability of SWOZ1, SWOZ2 and SWOZ2-BCNU cells. Conclusion: In conclusion, LINC00883 knockdown reduces drug resistance in glioma. Hence, our study provides a future strategy to prevent drug resistance-induced therapeutic failure in glioma.